Early Ukrainian settlements in Canada, 1895-1900 Dr. Josef Oleskow's role in the settlement of the Canadian Northwest, - Kaye, Vladimir J., 1896- (Canadian centennial series., 1964)
Dr. Kaye has set out to fill in some of the gap sin the story of the settlement of the Canadian West through this documentary history of the beginnings of Ukrainian settlement in Canada. He became interested in the history of settlement by various ethnic groups, especially those of Slavic origin, while serving in the Department of Citizenship and Immigration. This book contains a valuable compilation of original documents which provides students of the period with excellent source materials, and makes an important contribution to the history of the settlement of Manitoba and the Northwest Territories between 1895 and 1900. It will also assist in bringing about a better understanding of the nature of the Ukrainian agricultural immigration, and in correcting some common misconceptions. For example, Dr. Kaye points out that the Ukrainian economic migration has been erroneously compared with the Irish immigration a few decades earlier: the majority of the Irish immigrants were evicted, starving paupers, while many of the Ukrainians who migrated, during the period at least, were small land-owners attracted by promises of free land. The so-called "Galician immigration," was not, however, wholly of small landholders: a considerable proportion of the immigrants were peasants of means, and even included descendants noble families which had become impoverished through the centuries. The documents upon which this study is based, with their descriptions of the founding of colonies, the establishment of homes on remote homesteads, the destruction of meagre belongings of the early settlers by prairie fires, and the joys of harvesting the first crop, reveal the courage of these pioneers who faced difficulties with perseverance and patience that finally rewarded them with success. This book will be a valuable addition to the sociological, political, and historical studies of the Canadian West, and a previous record for Canadians of Ukrainian origin, who will find in it an accurate account of the beginnings of a movement so fateful for them and for Canada